Pengaruh Emisi Carbon Dan Green Innovation Terhadap Nilai Perusahaan - Fitriyah Fitriyah; Regina Deia Soeparyono (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
This study is motivated by the increasing global concern over environmental sustainability and its implications for corporate performance, particularly in carbon-intensive sectors such as energy. As stakeholders demand greater transparency and accountability, companies are expected to manage carbon emissions and adopt green innovation to enhance their value. This research aims to examine the effect of carbon emissions and green innovation on firm value, with additional consideration of carbon emission disclosure and media exposure. The study employs an associative quantitative approach using secondary data from 83 energy sector companies listed on the Indonesia Stock Exchange during the 2019–2023 period. The sampling method used is purposive sampling. Data were analyzed using panel data regression, along with model selection tests, t-tests, F-tests, and the coefficient of determination, supported by EViews 12 software. The empirical results show that carbon emission disclosure does not have a significant effect on firm value. Similarly, green innovation is found to have no significant effect on firm value. Furthermore, the results of the F-test indicate that carbon emission disclosure and green innovation simultaneously do not have a significant effect on firm value. In addition, the coefficient of determination shows a very low explanatory power of the independent variables on firm value. These findings suggest that firm value in the energy sector is more strongly influenced by other factors outside the model, highlighting the need for further research to include additional variables that may better explain firm value dynamics.